Is dietary supplement use longitudinally associated with fatigue in stage I-III colorectal cancer survivors?. Issue 1 (January 2020) - Koole, Janna L.; Bours, Martijn J.L.; Breedveld-Peters, José J.L.; van Roekel, Eline H.; Breukink, Stéphanie O.; Janssen-Heijnen, Maryska L.G.; Vogelaar, F. Jeroen; Aquarius, Michel; Keulen, Eric; Stoot, Jan; Weijenberg, Matty P.
Summary: Background & aims: Supplement use among colorectal cancer (CRC) survivors is common, yet evidence supporting its beneficial health effects is mostly lacking and cancer-specific lifestyle guidelines advise against the use of supplements. We aimed to describe the use of supplements by CRC survivors from diagnosis to 2 years post-treatment and investigate how overall supplement use is longitudinally associated with fatigue. Methods: In a prospective cohort study of stage I-III CRC survivors (n = 325), information on supplement use was collected during repeated home visits at diagnosis and at 6 weeks, 6, 12, and 24 months post-treatment. Fatigue was assessed using the Checklist Individual Strength (score range 20–140) at all post-treatment time points. Linear mixed-models were applied to analyze longitudinal associations of overall supplement use with fatigue, adjusted for sex, age, comorbidities, chemotherapy, and physical activity. Results: At all time points, about 40% of participants used supplements. Multivitamins/multiminerals were the most frequently used supplements at all time points. Of participants with at least two available measurements, 28% were consistent users, 45% consistent nonusers, and 27% inconsistent users (i.e. reported both use and nonuse). Reported fatigue levels declined significantly after treatment. Overall, no statistically significant differences in fatigue score over time were observed between supplement users and nonusers. Likewise, no intra-individual associations of supplement use and fatigue were found. However, in inter-individual analyses, supplement users reported to experience more fatigue compared to nonusers (β 7.0, 95% CI 0.3; 13.7). Conclusions: No overall association between supplement use and fatigue was found. Results of the current study do therefore not imply that supplement use alleviates complaints of fatigue among CRC survivors. However, increased levels of fatigue may be a reason for supplement use among CRC survivors.